125 Supplementing extra dietary DL-methionine mitigates effects of higher stocking density on growth performance, meat quality, and health status of broiler chicks. (5th December 2019) - Magnuson, Andrew; Liu, Guanchen; Sun, Tao; Tolba, Samar; Fahrenholz, Adam; Xi, L; Whelan, Rose; Lei, Xingen
Abstract: This study was to determine if 30% extra supplemental DL-methionine could improve growth performance, meat quality, and health status of broilers stocked at a high density. A total of 560 day-old male Cornish cockerel chicks were divided into 4 treatment groups: 2 stocking densities (2.9 and 3.8 kg/ft 2 ) and 2 supplementations of DL-methionine (grower: 2.90 or 3.77 g/kg and finisher: 2.60 or 3.38 g/kg). Chicks were fed the same corn-soybean meal-based starter diet and then experimental diets (grower: 6.4 g SAA/kg, finisher: 5.9 g SAA/kg, n = 10 pens/treatment). Growth performance and mortality were recorded, and blood and tissue samples (3 chicks/pen) were collected at the end of each period. Data were analyzed by two-way ANOVA. High stocking density decreased (P < 0.05) BW and (or) ADG of growers and finishers. Both high stocking density and methionine decreased (P < 0.05) ADFI and the high methionine improved (P < 0.05) feed use efficiency of chicks during the grower-finisher period. Neither treatment affected feather coverage, mortality, incidences of diseases, or dressing percentage. The high methionine improved (P < 0.05) meat to bone ratio of thigh, and exerted mixed effects (P < 0.05) on texture of breast and thigh. Dietary methionine and stocking density showed no major effects on tissue lipid profiles, but moderate effects (P < 0.05) on plasma concentrations of total cholesterol and(or) triglycerides of chicks. Fatty acid profiles in the liver and breast of chicks were unaffected by either treatment. The two treatments enhanced (P < 0.05) tibial maximum breaking strength (15–20%) and plasma alkaline phosphatase activity of growers. In conclusion, the high stocking density affected growth performance, meat quality, and health status of broilers. Supplementing 30% extra dietary methionine seemed to mitigate some of those effects. (Supported in part by Evonik Nutrition & Care GmbH, Germany)